Assessment of mechanical performance of sustainable structural mud insulated panels - Khan, Asad; Adil, Mohammad; Dan, Danhui; Khan, Muhammad Adeel; Ahmad, Mahmood; Khan, Muhammad Salman; Sabri, Mohanad Muayad Sabri (Frontiers in Materials, 2024)
Composite construction materials are extensively employed and have proven to be more effective than their individual components, such as steel and concrete. This is because composites combine the strengths of different materials, resulting in enhanced properties such as increased strength-to-weight ratios, better durability, and improved thermal efficiency. However, despite the strong structural properties and energy-saving benefits of reinforced concrete sandwich panels, their use is restricted in many rural regions of developing nations like Pakistan, largely because of the economic limitations faced by the communities. Therefore, this study introduces cost-effective structural mud insulated panels (SMIPs) that utilize mud wythes and evaluates their mechanical performance. These panels consist of a lightweight Expanded Polystyrene (EPS) foam core, sandwiched between two galvanized steel-reinforced mud layers. The study includes flexural, compression, diagonal tension, and water absorption tests. Flexural tests revealed that the panels have substantial load-bearing capacity under bending forces. Whereas, Compression tests showed that the panels possess adequate strength and stiffness to support moderate structural loads. Additionally, Diagonal tension tests confirmed the panels' ability to resist significant in-plane loads. Water absorption tests also indicated that the panels demonstrated adequate moisture resistance, staying within the acceptable limit of 15%. These findings highlight the mechanical and hydric properties of SMIPs, underscoring their potential in sustainable construction, especially in economically constrained regions.